DIAGNOSIS DAN PENGOBATAN MALARIA VIVAX KONGENITAL: LAPORAN KASUS - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1994)
A case of 29 days old infant with high fever has been brought to Dr. Sardjito General Hospital seeking for treatment. Sepsis was suspected and treatment with antibiotics had been given. No response was observed despite the course of antibiotics. Diagnosis of malaria vivax was made atter rings and trophozoits had been spotted in the periphery blood slides. Congenital vivax malaria was therefore diagnosed. A single oral dose of fansidar was given with caution. No malaria parasites were found in the blood slides three days post treatment and during visits for checking after hospital discharge. No side effects of treatment was found.